ANALISIS KUALITAS LAYANAN PORTAL kemahasiswaan.ft.unp.ac.id MENGGUNAKAN METODE WEBQUAL 4.0 (Studi Pada Mahasiswa Fakultas Teknik Universitas Negeri Padang Sebagai Pengguna Portal Kredit Ekstrakulikuler) - Siti Muthmainnah; Legiman Slamet; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
Portal kemahasiswaan.ft.unp.ac.id as information service provider on student’s credit points should’ve good quality on services, not only in information but also in interactions between user and interface on between user and admin. This research aims to provide how good the service quality which give of portal in fulfill student’s necessary. The method used is webqual 4.0 method that includes four dimensions that is usability dimension, information quality, quality of services interaction and overall. Sampel of the researchis 98 students. Sampel determining by random and proportional levels. Data were collected throught a questionnaire. Containing statements about student’s perceptions of portal. The data will be processed to obtain the webqual index (WQI) values which use to determining the value of service quality. The analysis showed that the service quality of portal kemahasiswaan.ft.unp.ac.id is good which value of webqual index (WQI) scale is 0,73. The value of each dimension are usability is 0,75; information quality is 0,73; quality of services interaction and overall is 0,71. The factors that influence service quality of portal is usability dimension, it seen by value of WQI scale is 0,75.  Keywords: WIFI@UNP, Fuzzy-Servqual, gap.